POSITIVE POLITENESS STRATEGIES FOUND IN THE “BEAUTY AND THE BILLIONAIRE” MOVIE - Sukariyani, Ni Ketut; Maharani, Putu Devi (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
The concept of politeness is very important in human interaction, because it can foster harmonious communication and relationships. This research explores one type politeness strategy found in "Beauty and the Billionaire" movie, that called positive politeness. This research aims to identify the types of positive politeness strategies used by the characters. It uses a qualitative descriptive method to analyze dialogue data from the film. Research findings reveal the application of various positive politeness based on theory, starting from the most dominant ones, namely Give gifts to hearer, Exaggerated, Offer or promise, Intensify interest to the hearer, Give or ask for the reason, Be optimistic, Use in group identity markers, Avoid disagreement, Include both speaker and hearer in the activity. The results provide insight into how characters in films use positive politeness to maintain and improve social relationships.